Changes in HIV post-exposure prophylaxis prescriptions before and after the introduction of HIV pre-exposure prophylaxis at a sexual health clinic in Melbourne, Australia, 2011-2021 - Ranjit S. Samra; Christopher K. Fairley; Jason J. Ong; Ei T. Aung; Eric PF. Chow (Elsevier, 2024)
Objective: HIV pre-exposure prophylaxis (PrEP) became available in Victoria, Australia, in 2016. We examined non-occupational post-exposure prophylaxis (nPEP) usage among gay, bisexual and other men who have sex with men (MSM) before and after PrEP became available. Methods: We included MSM attending Melbourne Sexual Health Centre for nPEP between 2011 and 2021. We analysed three periods: the 'pre-PrEP' (01 Jan 2011 to 25 Jul 2016), 'PrEP before COVID-19' (26 Jul 2016 to 31 Dec 2019), and 'PrEP during COVID-19' (01 Jan 2020 to 31 Dec 2021). Results: There were 222,978 consultations for MSM; 8292 (3.7%) were nPEP consultations. The proportion of nPEP consultations increased from 3.3% (3093/94263) in the pre-PrEP period to 4.3% (3843/89251) in the PrEP before COVID-19 period then dropped to 3.4% (1356/39464) during the COVID-19 period. Compared to Australian-born MSM, MSM born in Central/South America (adjusted odds ratio [aOR]: 1.75; 95% confidence interval [CI]: 1.27-2.40) had the highest odds of accessing nPEP, followed by Asian-born MSM (aOR: 1.47; 95% CI: 1.27-1.71) after adjusting for PrEP availability and COVID-19. Those newly arrived in Australia in ≤4 years had higher odds (aOR: 1.14; 95% CI: 1.05-1.22) of accessing nPEP than those living in Australia for >4 years. Conclusion: nPEP prescriptions declined with PrEP availability. Newly arrived overseas-born MSM who are unlikely to have access to subsidised PrEP have a higher demand of nPEP. Implications for Public Health: Increasing PrEP education and ensuring equal access is vital in the drive to reduce new HIV diagnoses.